A rare Krukenberg tumor arising from a primary adenocarcinoma of the small intestine - Angel An-Chieh Liu; Chi-Huang Chen; Wei-Min Liu; Ching-Wen Chang (Elsevier, 2018)
Objective: A Krukenberg tumor is a malignancy in the ovary that metastasizes from a primary site. Here, we report a very rare case of bilateral Krukenberg tumors of the ovaries arising from a primary adenocarcinoma of the small intestine in a 53-year-old Taiwanese woman. Case report: The patient presented with a 3-month history of abdominal distension and acid regurgitation. Gastroscopy and colonoscopy findings were negative. According to the preoperative image, we highly suspected that the small bowel mass was the primary tumor with metastatic tumors to bilateral ovarian masses. The diagnosis was made immediately after operation. Results from pathology and immunohistochemical report confirmed our diagnosis. Conclusion: The primary lesion of a Krukenberg tumor is generally too small to be detected. Thus, careful radiographic and endoscopic exploration of the digestive system is necessary to detect the primary tumor. Immunohistochemical evaluation is also useful for determining the primary site of the adenocarcinoma. Keywords: Adenocarcinoma, Immunohistochemical evaluation, Krukenberg tumor, Small intestine, Preoperative computed tomography